Necrolytic migrating erythema as a diagnostic marker of pancreatic cancer - M. M. Tlish; Zh. Yu. Naatyzh; T. G. Kuznetsova; D. I. Masko; Ya. V. Kozyr (Лечащий Врач)
Paraneoplastic syndromes include diseases that arise as a result of the development of a malignant neoplasm, manifested by symptoms that are remote from the localization of the tumor itself and its metastases. Paraneoplastic dermatoses are a large group of various skin manifestations that indicate the possibility of the presence of a tumor, including at an early asymptomatic stage of development. One of these dermatoses is necrolytic migrating erythema, a skin pathology associated with glucagonoma, an alpha – cell tumor of the pancreas that produces glucagon. The description of the clinical case presented in the article will help to improve the understanding of the common pathogenetic aspects between neoplasm and dermatosis, increase the oncological alertness of related specialists and organize effective interdisciplinary interaction, as a result, improving the quality of life of patients with tumor-associated dermatoses.